The Influence of Workload and Career Development on Work Performance at the Central Statistics Agency of Palembang City - Putri Wulandari; Harahap, Lily Rahmawati; Ermeila, Sri (Universitas Dehasen Bengkulu, 2025)
This study aims to evaluate the effect of workload and career development on employee performance at BPS Palembang city, both together and separately. The approach used is quantitative, with primary data obtained through distributing questionnaires to 41 respondents who are employees of BPS Palembang city. The data collected were then analyzed using multiple linear regression methods to identify the relationship between the independent variables (workload and career developmet) and the dependent variable (work performance). The results of the study indicate that workload has a positive and significant effect on employee performance, while career development does not show a significant effect. This finding is supported by the regression coefficient value for workload of 0,295 with a significance level below 0.05. in contrast, career development has a regression coefficient of 0.033 with a significance value of 0.821, which exceeds the threshold of 0.05. the resulting regression equation is Y = 26.960 + 0.295X1 + 0.033X2, where X1 refers to workload and X2 to career development.